Žemaitė’s Feminism - Čiočytė, Dalia (Literatūra, 2009)
The biography of Julija Beniuševičiūtė-Žymantienė – Žemaitė (1845–1921), one of the greatest Lithuanian Realists, has got a broad accent of feminist activity. Some short stories written by Žemaitė express feminist ideas with publicistic pathos (In Town, „Mieste“, 1905, Mister Zigmantas, „Ponas Zigmantas“, and others). In her short story Eve („Ieva“) Žemaitė presents an interesting ironic interpretation of the biblical archetype. Žemaitė’s best literary visions of women’s infelicity varies the topos of a quiet / silent / silenced woman and interestingly imply some gap between feminist ideology and literary meaning. In the short stories The Daughter-in-Law („Marti“, 1896), They Didn’t Have a Good Mother („Neturėjo geros motinos“, 1895) the reason of misfortunes seems to be deeper than just women being oppressed by men in the patriarchal society. The patriarchal oppression of women is constructed as a metonymy of the philosophical evil. The short story Sutkai (1897) may be interpreted as a literary vision of a feminine utopia: woman’s identity here is defined rather as wholeness than “otherness”.